2014
DOI: 10.1002/bjs.9519
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing Nordic pole walking and a standard home exercise programme in patients with intermittent claudication

Abstract: ISRCTN78168304 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 27 publications
2
53
0
3
Order By: Relevance
“…17,18 Similarly another two publications related to the reporting of the early and late results from one clinical trial. 19,21 Two further full text publications were excluded because they did not include PAD patients or because they reported a review article. Ultimately, five clinical trials reported in five publications were included ( Fig.…”
Section: Selection Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Similarly another two publications related to the reporting of the early and late results from one clinical trial. 19,21 Two further full text publications were excluded because they did not include PAD patients or because they reported a review article. Ultimately, five clinical trials reported in five publications were included ( Fig.…”
Section: Selection Of Included Studiesmentioning
confidence: 99%
“…Three of the trials delivered supervised Nordic walking programmes at a central facility, 18,20,24 one trial used a combination of supervised and unsupervised Nordic walking sessions, 17 and one trial assessed a home based exercise programme with telephone support. 19,21 The control group in each trial also varied. In three of the trials, in which the Nordic walking programme was fully supervised, the control group was allocated to a supervised exercise programme of standard walking which was performed on treadmills in two of the three trials.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The number of participants in both works of research carried out in the United Kingdom was comparatively lower: initially 52 patients were included in the research of Spafford et al (2014), but only 38 patients were involved in the final analysis (n=19 in each group; the average age 65±2 years; there is no data about the gender proportion for the analysed group). 21 patients were analysed in the research of Oakley et al (2008) (men, the average age 70 years (from 57 to 79)).…”
Section: Resultsmentioning
confidence: 99%
“…In both researches of Collins et al the supervised training regime was applied. In the research of Spafford et al (2014) patients were trained and instructions were provided to perform individual training at home at least 30 minutes 3 times per week for 12 weeks (the execution was controlled with a pedometer and a diary), the patients were motivated and supported by telephone calls of the physiotherapist once a week, as well as the patients were controlled every 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation